Porcine sapelovirus 2A protein induces mitochondrial-dependent apoptosis - Mou, Chunxiao; Wang, Yuxi; Pan, Shuonan; Shi, Kaichuang; Chen, Zhenhai (Frontiers in Immunology, 2022)
Porcine sapelovirus (PSV) is an emerging pathogen associated with symptoms of enteritis, pneumonia, polioencephalomyelitis and reproductive disorders in swine, resulting in significant economic losses. Although PSV is reported to trigger cell apoptosis, its specific molecular mechanism is unclear. In this research, the cell apoptosis induced by PSV infection and its underlying mechanisms were investigated. The morphologic features of apoptosis include nuclear condensation and fragmentation, were observed after PSV infection. The cell apoptosis was confirmed by analyzing the apoptotic rates, caspase activation, and PARP1 cleavage. Caspase inhibitors inhibited the PSV-induced intrinsic apoptosis pathway and reduced viral replication. Among the proteins encoded by PSV, 2A is an important factor in inducing the mitochondrial apoptotic pathway. The conserved residues H48, D91, and C164 related to protease activity in PSV 2A were crucial for 2A-induced apoptosis. In conclusion, our results provide insights into how PSV induces host cell apoptosis.